Solar-driven novel methane reforming with carbon looping for hydrogen production. (20th September 2019) - Qiu, Jingwen; Zhu, Lin; Li, Luling; He, Yangdong; Zhou, Minghui
Abstract: As a renewable source, solar energy plays an important role in meeting energy demand for human beings and in relieving global warming. In this paper, the concentrated solar heat is utilized to drive the high-endothermic methane reforming with carbon looping. In so doing, the process increases the utilization of CO2 and reduces the carbon emissions as well as saves the extra fuel consumption for combustion, leading to high efficiency of energy utilization. By optimizing this proposed system, the energy efficiency can reach approximate 67.13% with simultaneously reducing CO2 emissions by 34.98% compared with SMR process. Exergy analysis is used to assess the location of irreversibility within process. The maximal part of exergy destroyer was localized in reformer with a contribution of 68%. In addition, the effects of hourly variation of direct normal irradiation on thermodynamic performance and methane conversion on the four typical days (spring equinox, summer solstice, autumn equinox, winter solstice) were analyzed in this work. The current work might be insightful for solar-hydrogen production field. Highlights: A mid-temperature solar fuel system by combining with carbon-looping combustion was proposed for hydrogen production. The hourly variation of DNI and the solar share on the four seasons were analyzed. The efficient use of carbon dioxide as well as the improvement of energy efficiency were achieved.